Development of a basic Group Support System (GSS) and assessing the impact of its implementation in Bangladeshi organization - Humaira Binta Kamal (BRAC University, 2010)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2005.